IMPLEMENTASI PENETAPAN ALAT BUKTI YANG CUKUP DALAM UNSUR MERUGIKAN KEUANGAN NEGARA BERDASARKANUNDANG-UNDANG NOMOR 20 TAHUN 2001 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 31 TAHUN 1999 TENTANG PEMBERANTASAN TINDAK PIDANA KORUPSI - Ragilio, Fadhil Mu’amar (Journal of Law ( Jurnal Ilmu Hukum ), 2018)
ABSTRACT The calculation and determination of state financial losses is one of the most frequent and controversial issues in the settlement of corruption cases. Each law enforcement officer often provides different interpretations, particularly those related to which agency has the authority to calculate and determine the amount of the state's financial loss in a court decision.In the Anti-Corruption Eradication Act which is the principal to determine a person as a suspect is the element of state losses. Meanwhile, in determining the element of state losses, it is necessary to calculate the losses incurred. The calculation of such losses if we refer to Article 184 Criminal Procedure Code can be categorized as letter proof. So in the determination of criminal acts of corruption based on at least 2 (two) evidences need to be considered documentary evidence in the form of calculation of state losses from the institution authorized to assign a person as a suspect.It is necessary to stipulate the party that can determine the state losses other than the CPC and BPKP as stated in the Constitutional Court Decision Number 31 / PUU-X / 2012 dated October 23, 2012 stipulated that in order to prove a criminal act of corruption, the Corruption Eradication Commission (KPK) can only coordinate with BPKP and BPK, but can also coordinate with other agencies, can even prove themselves outside the findings of BPKP and BPK, for example by inviting experts or by requesting material from the inspectorate general or body that has the same function with it. Keywords: Finance, Corruption, Suspect, Evidence